TINDAK PIDANA KEKERASAN TERHADAP ISTRI DALAM RUMAH TANGGA MENURUT UNDANG-UNDANG NO. 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (STUDI PUTUSAN PENGADILAN NEGERI KABANJAHE NO. 128/PID.SUS/2016/PN KBJ) - Omega Satrio Ginting; Maslon Hutabalian; Rayani Saragih (Journal Recht (JR), 2022)
This study discusses the Crime of Violence Against Wives in the Household According to Law no. 23 of 2004 concerning the Elimination of Domestic Violence (Study of the District Court of Kabanjahe No. 128/Pid.Sus/2016/Pn Kbj. The purpose of this study is to determine the provisions governing criminal acts of domestic violence and obstacles in law enforcement of acts of domestic violence). criminal acts of violence against wives in the household and to find out the law enforcement against domestic violence based on the study of decision No.128/Pid.Sus/2016/PN Kbj Kabanjahe District Court.This type of legal research is carried out by normative juridical methods, namely legal research conducted by examining materials literature or secondary data as the basic material to be researched by conducting a search of the regulations and literature relating to the problem under study. The results of this study indicate that the provisions of Law Number 23 of 2004 concerning domestic violence not only protect husbands or wives, but also protect all family members who live in one house, including a housemaid. Elimination of domestic violence is a guarantee given by the state to prevent domestic violence, take action against perpetrators of domestic violence, and protect victims of domestic violence